The Efficacy of the Minimally Invasive Lumbar Decompression (MILD®) Procedure: A PRISMA-compliant Systemic Review and Meta-analysis - Zhang, Xin-yu; Zhao, Jian-li; Wang, Ya-jing; Luan, Jie; Lin, Hong-qi; Wang, Dajie (Pain physician, 2025)
BACKGROUND: Lumbar spinal stenosis is the most common cause for spinal surgery of older adults. It is associated with pain in the legs and back as well as impaired ambulation. Minimally Invasive Lumbar Decompression (MILD®, Vertos Medical) is a percutaneous, image-guided lumbar decompression technique for central canal stenosis secondary to a hypertrophied ligamentum flavum. However, whether MILD can achieve adequate beneficial results in patients with lumbar spinal stenosis remains undetermined. OBJECTIVE: To assess the efficacy and complications of MILD for lumbar spinal stenosis. STUDY DESIGN: A systematic review and meta-analysis. METHODS: Electronic databases were searched to identify all clinical trials of patients undergoing MILD surgery. Primary outcomes included Visual Analog Scale scores (VAS) or Oswestry Disability Index scores (ODI) at baseline, < 6 months posttreatment, <= 6 months posttreatment, < one year, and >= one year posttreatment. Secondary outcomes included postoperative complications. For continuous variables, the treatment effects were calculated by weighted mean difference and 95% CI. The statistical significance was defined as P < 0.05. RESULTS: There were 334 trials identified; 12 of them, with data from 500 patients, were included in our analysis. MILD treatment resulted in a significant decrease in the mean pain score compared to the baseline (P < 0.01). There is a consistent pattern of decreased mean ODI scores following MILD compared to the baseline (P < 0.01). LIMITATIONS: The included MILD clinical trials did not have the same exclusion and inclusion criteria. While all clinical trials in this study adopted conservative treatments prior to MILD, there were no standardized treatment modalities and length of time. All of the studies employed subjective outcome tools including VAS and ODI. However, these self-reported outcome tools are subject to bias. CONCLUSIONS: Our study suggests MILD is an effective and safe surgical technique for patients with stenosis from ligamentum flavum hypertrophy. This technique resulted in significant clinical improvement, as indicated by changes in pain scores and ODI scores. In addition, adverse events were low compared to other surgical decompression techniques. To further confirm this, more well designed and powered randomized trials are needed. KEY WORDS: Spinal stenosis, lumbar spine, decompression, stenosis, minimally invasive decompression, Visual Analog Scale score, Oswestry Disability Index, side effects